Given that a b − 1 5 and a + b − 8 are integers. And that
a 2 b 2 + 1 6 a + 1 6 b + 8 0 = a 2 + 3 2 a b + b 2
Find a 2 + b 2 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
So a and b are 4+ sqrt(8)i and 4 - sqrt(8)i
a 2 b 2 + 1 6 a + 1 6 b + 8 0 a 2 b 2 − 3 0 a b + 8 0 ( a b − 1 5 ) 2 ( a b − 1 5 ) 2 = a 2 + 3 2 a b + b 2 = a 2 + 2 a b + b 2 − 1 6 ( a + b ) = ( a + b − 8 ) 2 + 8 1 = ( a + b − 8 ) 2 + 3 4 As a b − 1 5 and a + b − 8 are integers, ( a b − 1 5 ) and ( a + b − 8 ) are perfect square, which means that ( a b − 1 5 ) 2 and ( a + b − 8 ) 2 are integers power of 4 ( E x p : 0 , 1 , 1 6 , 8 1 , … ). By Fermat Last Theorem, there does not exist postive integer solution for x 4 + y 4 = z 4 . As ( a b − 1 5 ) and ( a + b − 8 ) are nonnegative, we can conclude that a + b − 8 = 0 and ( a b − 1 5 ) 2 = 3 4 .
We get ( a + b = 8 ) and ( a b = 2 4 ). a 2 + b 2 = ( a + b ) 2 − 2 a b = 6 4 − 2 × 2 4 = 1 6 The answer is 1 6 .
a b = 2 4 not 2 6
Problem Loading...
Note Loading...
Set Loading...
Let a b − 1 5 = m and a + b − 8 = n , where m and n are integers. Then a b = m 2 + 1 5 and a + b = n 2 + 8 and
a 2 b 2 + 1 6 a + 1 6 b + 8 0 ( a b ) 2 + 1 6 ( a + b ) + 8 0 ( m 2 + 1 5 ) 2 + 1 6 ( n 2 + 8 ) + 8 0 m 4 + 3 0 m 2 + 2 2 5 + 1 6 n 2 + 1 2 8 + 8 0 m 4 = a 2 + 3 2 a b + b 2 = ( a + b ) 2 + 3 0 a b = ( n 2 + 8 ) 2 + 3 0 ( m 2 + 1 5 ) = n 4 + 1 6 n 2 + 6 4 + 3 0 m 2 + 4 5 0 = n 4 + 3 4
By Fermat last theorem , positive integer solution does not exist for x 4 + y 4 = z 4 . Therefore, n = 0 and m = 3 ; and a b = 2 4 and a + b = 8 , ⟹ a 2 + b 2 = ( a + b ) 2 − 2 a b = 8 2 − 2 ( 2 4 ) = 1 6 .